2021
DOI: 10.1017/9781108779210
|View full text |Cite
|
Sign up to set email alerts
|

Brecht and Tragedy

Abstract: This wide-ranging, detailed and engaging study of Brecht's complex relationship with Greek tragedy and tragic tradition argues that this is fundamental for understanding his radicalism. Featuring an extensive discussion of The Antigone of Sophocles (1948) and further related works (the Antigone model book and the Small Organon for the Theatre), this monograph includes the first-ever publication of the complete set of colour photographs taken by Ruth Berlau. This is complemented by comparatist explorations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Cittilin A and B are commonly found in extracts derived from the species M. xanthus including the model strain DK1622, as judged on the basis of high-resolution LC–MS data from myxobacterial secondary metabolome studies. , We first verified the structures of cittilin A and B using NMR spectroscopy, since no analytical data for these compounds isolated from myxobacteria was available in the literature (Supporting Information). Our analysis confirmed that the structure of myxobacterial cittilin B is identical to RP-66453 from Streptomyces strain 9738 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Cittilin A and B are commonly found in extracts derived from the species M. xanthus including the model strain DK1622, as judged on the basis of high-resolution LC–MS data from myxobacterial secondary metabolome studies. , We first verified the structures of cittilin A and B using NMR spectroscopy, since no analytical data for these compounds isolated from myxobacteria was available in the literature (Supporting Information). Our analysis confirmed that the structure of myxobacterial cittilin B is identical to RP-66453 from Streptomyces strain 9738 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%